Environmental Ethics in Bima Local Wisdom: An Analysis from the Perspective of Seyyed Hossein Nasr - Husnatul Mahmudah; Zuhrah Zuhrah (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
This research aims to examine the environmental ethics contained in the local wisdom of the Bima people and relate them to the perspective of Islamic philosophy. The focus of this study is based on the local traditions of the community not only having a social function but also loaded with philosophical and spiritual dimensions relevant to Islamic ethics. The research method used is qualitative with an ethnographic-philosophical approach. Data collection was done through in-depth interviews with community leaders, Foccus Group Discussion, field observations, and literature studies. The results of the study show that the environmental ethics of the Bima community include: (1) harmony with nature; (2) Environmental conservation; (3) Sustainable utilization; and (4) socio-ecological responsibility. These values have strong relevance to the teachings of tauhid, the principle of balance (al-mizan), and human responsibility (khalifah) in Islamic philosophy, especially as affirmed in Seyyed Hossein Nasr's thoughts on ecosufism and the sacredness of nature as manifestations of the divine. This research emphasizes that the local wisdom of the Bima people is not just an ecological tradition, but a philosophical praxis that brings together Islamic values with the ecological experience of the community. The implications of the findings of this research can be a foundation in the formulation of regional environmental policies, especially in Bima as well as for strengthening environmental education based on local wisdom and contextual community empowerment programs.